Penerapan Algoritma Filtering Derivatif Untuk Penajaman Kualitas Pada Citra - Khairul, Khairul (Jurnal Sistem Komputer dan Informatika (JSON), 2020)
Derivative filtering algorithm is the formulation of mathematical derivative concepts beginning with understanding the concepts of calculus applications, especially differential theory (derivatives) in digital formulations. The method used in the formulation of this theory is to seek, collect and study several theories related to differences and their applications. The derivation technique can be described as calculating the rate of brightness values in a discrete digital image, also known as an image derivation technique. Sharpening will be obtained by calculating the difference in brightness values between adjacent brightness values in the same column and row. Image is the overall result of a data recording system. Theoretically, images can be grouped into 2 (two) types, namely continuous images and discrete images (digital images). A continuous image is generated from an optical system that receives an analog signal. Example: human eye, analog camera. Meanwhile, digital images are generated through the process of digitizing continuous images. Example: digital camera.